2006
DOI: 10.1128/jcm.00421-06
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Clinical Herpes Simplex Virus Type 1 Isolates by Use of Restriction Enzymes

Abstract: Recently, three distinct genotypes of clinical herpes simplex virus type 1 (HSV-1) isolates were identified based on DNA sequence information and phylogenetic analysis of clinical isolates and laboratory strains. We utilized single-nucleotide polymorphism within the genes coding for glycoproteins G and I for rapid genotype classification by PCR and restriction enzyme cleavage. The method is suitable for high-scale genotyping of clinical HSV-1 isolates and for the detection of recombinants.Herpes simplex virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 13 publications
2
44
0
Order By: Relevance
“…3) and can be categorized as changes where strains F and H129 share the same amino acid residue with each other, but differ from strain 17, versus those positions where only strain H129 or strain F has a unique amino acid relative to the other two strains (see Table S2 for a full list of all amino acid differences for each protein). In a prior analysis using a limited number of genes, Norberg and colleagues found that strain 17 and strain F were divergent enough to fall into distinct clades (47,48). Since these clades are distinguishable based on restriction digest patterns in the US4 and US7 genes (48), we applied this approach and found that strain F and strain H129 fall into the same clade, while strain 17 does not (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…3) and can be categorized as changes where strains F and H129 share the same amino acid residue with each other, but differ from strain 17, versus those positions where only strain H129 or strain F has a unique amino acid relative to the other two strains (see Table S2 for a full list of all amino acid differences for each protein). In a prior analysis using a limited number of genes, Norberg and colleagues found that strain 17 and strain F were divergent enough to fall into distinct clades (47,48). Since these clades are distinguishable based on restriction digest patterns in the US4 and US7 genes (48), we applied this approach and found that strain F and strain H129 fall into the same clade, while strain 17 does not (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, variant calls showing a directional strand bias of Ն0.85 were excluded from further analyses. Consensus sequences were generated for each rash sample, but iterative repeat regions R1, R2, R3, R4, and R5 (19,20) as well as the terminal repeat region were trimmed prior to tree-building analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated that homologous recombination contributes significantly to the evolution of many herpesviruses, including HSV-1 (12,(18)(19)(20)(21). Recent complete genome analysis of HSV-1 strains suggests that all or most wild-type strains have recombinant mosaic genomes (22,23).…”
mentioning
confidence: 99%
“…Journal of General Virology 89 Nahmias et al, 2006;Norberg et al, 2004;Sakaoka et al, 1994;Umene, 1998;Umene & Kawana, 2003;Umene & Sakaoka, 1999;Umene et al, 2007). Variations in restriction endonuclease cleavage patterns between HSV-1 isolates have been analysed and a number of restriction fragment length polymorphisms (RFLPs) detected (Norberg et al, 2006;Sakaoka et al, 1994;Umene & Yoshida, 1993). An RFLP is usually due to a nucleotide substitution that causes the gain or loss of a restriction endonuclease cleavage site.…”
Section: Introductionmentioning
confidence: 99%